The Potential of Hydrocyclone Application for Mammalian Cell Separation in Perfusion Cultivation Bioreactors - Elsayed, Elsayed A.; Wadaan, Mohamad A. (International Journal of Biotechnology for Wellness Industries, 2013)
Hydrocyclones have been traditionally applied for long times in many industrial fields, such as in mineral processing and mining, chemical and petrochemical, and food industries. They have many characteristics that favor them as separation system in solid/liquid, gas/liquid and liquid/liquid processes. During the last two decades, they have been evaluated for their possible application in the separation of microbial and mammalian cells. Nowadays, mammalian cells are widely used for the production of a large number of valuable therapeutic proteins, antibodies, hormones and vaccines. This review highlights the potential of the application of hydrocyclones for mammalian cell separation in continuous perfusion biorecators. The discussion will cover the structure of hydrocyclone, mechanism of separation inside hydrocyclones, different theories describing the separation process, as well as the effect of changing different geometrical variables on the efficiency and performance of the separation process. Furthermore, we will focus on the latest developments achieved in the field of separation of living cells in both laboratory and pilot plant cultivation scales.